Slow progression of dentin bond degradation during one-year water storage under simulated pulpal pressure - Belli, Renan; Sartori, Neimar; Peruchi, Lais Dalmagro; Guimaraes, Jackeline Coutinho; Araujo, Elito; Monteiro, Sylvio; Baratieri, Luiz Narciso; Lohbauer, Ulrich (Journal of Dentistry, 2010)
Objectives: To evaluate the dentin bond durability of simplified adhesives after one-year (1 y) under water storage and simulated pulpal pressure. Methods: Class I cavities were prepared in sixty human third molars with the pulpal wall located in mid-coronal dentin. The roots were cut off to expose the pulpal chamber, and the teeth were assembled in a pulpal pressure simulator device. A two-step etch-and-rinse adhesive (Single Bond 2/SB), a two-step self-etch adhesive (Clearfil SE Bond/CSE), a three-step self-etch adhesive (Adper Scotchbond SE/SSE) and three all-in-one adhesives (Adper Easy Bond/EB, Clearfil S3 Bond/S3 and Adhese One/AO) were applied according to manufacturers instructions. No enamel pre-etching was used for the self-etch systems. The cavities were filled with a composite (Z250, 3M ESPE) in four to five horizontal increments and individually cured. Immediately after the final cure, pulpal pressure was set to 15 cm H2O. After 24 h and 1 y under simulate pulpal pressure the teeth were cut following a 'nontrimming' microtensile test technique (n = 30) and tested in tension. Kruskall-Wallis and post hoc multiple comparisons were used at α = 0.05. Weibull statistics was applied to SB, CSE and EB. Fractographic analysis of debonded specimens was performed using scanning electron microscopy. Results: At 24 h and 1 y periods, SB showed higher bond strength means than all the others adhesives tested. CSE was not statistically different from EB at 24 h and from EB and SB at 1 y. EB showed bond strength statistically higher than the other three self-etch adhesives, which were not statistically different from each other at 24 h. AO showed significantly lower bond strength than all tested materials after 1 y. For all adhesives the mean bond strength at 1 y were not statistically different from the values measured at 24 h (p > 0.05). Shifts in failure mode patterns and Weibull modulus decrease indicate some degree of bond degradation after the 1 y storage period. Conclusion: One-year of simulated pulpal pressure did not affect dentin bond strength of simplified adhesives in Class I restorations. Signs of degradation were only revealed by fractographic analysis and reliability parameters. © 2010 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Adhesive; Bond; Degradation; Dentin; Durability; One-step; Pulpal pressure; Self-etch; Simulated